1988
DOI: 10.1302/0301-620x.70b3.3372567
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction of the severely slipped upper femoral epiphysis

Abstract: The results of open reduction of the severely slipped upper femoral epiphysis are reported for 1 15 hips with an average follow-up of 12 years 11 months (range 2 to 33 years). In 70 hips with a chronic slip and an open growth plate the incidence of complications was low: two developed avascular necrosis, five chondrolysis, and one had both. There were more complications in the 38 hips with an acute-on-chronic slip: six developed avascular necrosis, one chondrolysis, and three had both. Of the seven hips operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…4). Others have reported comparable results with 3% of OA at a mean 13-year followup using the original Dunn reduction procedure in a publication of its originator [10]. Using the cuneiform neck osteotomy, OA at a mean 13-year followup was found in 9% of the hips [21].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…4). Others have reported comparable results with 3% of OA at a mean 13-year followup using the original Dunn reduction procedure in a publication of its originator [10]. Using the cuneiform neck osteotomy, OA at a mean 13-year followup was found in 9% of the hips [21].…”
Section: Discussionmentioning
confidence: 88%
“…In these two studies, each study reported one hip converting to THA at short-term followup of 2 years (percentage of conversion to THA of 2% and 7%) [52,56]. With a minimal 10-year followup, other studies reported on a rate of conversion to THA after subcapital osteotomies ranging from 1% to 11% [6,10,50,71,72] (mean followup ranging from 10 to 16 years) and from 0% to 13% for intertrochanteric osteotomies (mean followup ranging from 19 to 24 years) [24,57,69]. Carney et al [12] evaluated several surgical treatments for hips with SCFE including in situ pinning and hips without surgical treatment and found a conversion to THA in 37% at a mean followup of 41 years.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of chondrolysis after the placement of implants for periarticular soft-tissue or fracture fixation, a history of joint trauma, and surgical insult with or without improper techniques have been reported across all joints [1][2][3]13,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][31][32][33][34][35][45][46][47][48]51,[53][54][55][56][57][58][59][60][61][63][64][65][66]69,70,[72][73][74][75][76][77][78][79]…”
Section: Potential Etiologic Contributors To Joint Chondrolysismentioning
confidence: 99%
“…basi-cervical and sub-capital), the greater the potential for correction of chronic slip deformity in SCFE [56]; however, there is an increased risk of osteonecrosis and chondrolysis [57]. For example, osteonecrosis has been reported to occur at a rate of 10-100 % [58][59][60].…”
Section: Scfementioning
confidence: 99%